Critical Child Protection Studies - Parton, Nigel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Up until the latter years of the twentieth century, there was very little critical analysis of child protection policies and practices. The core assumption was that it was concerns about child abuse and neglect that provided the rationale and focus for child protection policies, practices, and systems, and they were assumed to be benign in both intent and impact. Increasingly, however, it has been recognised that a whole range of political, cultural, and sociological influences bear on the development and operation of child protection policies, practices, and systems and that these can have a whole range of negative consequences. The aim of this edited book, based on the Special Edition of the same title, is to provide a range of international cutting-edge papers that critically analyse different aspects of child protection, and which also provide suggestions about how child protection can be positively reformed.